Respuesta :
so hmmm as you may know by now... [tex]\bf \begin{array}{cccccllllll}
{{ a}}^2& + &2{{ a}}{{ b}}&+&{{ b}}^2\\
\downarrow && &&\downarrow \\
{{ a}}&& &&{{ b}}\\
&\to &({{ a}} + {{ b}})^2&\leftarrow
\end{array}\qquad
% perfect square trinomial, negative middle term
\begin{array}{cccccllllll}
{{ a}}^2& - &2{{ a}}{{ b}}&+&{{ b}}^2\\
\downarrow && &&\downarrow \\
{{ a}}&& &&{{ b}}\\
&\to &({{ a}} - {{ b}})^2&\leftarrow
\end{array}[/tex]
is a perfect square trinomial
now, let's take a closer look at the middle guy
is just 2 * guy on the left * guy on the right
so the middle term is just the product of the two terms of the binomial, without the exponent, or square rooted, and 2
alrite... that said.... now let's do some grouping
[tex]\bf g(x)=3x^2+30x+72\implies g(x)=(3x^2+30x)+72 \\\\\\ g(x)=3(x^2+10x)+72\implies g(x)=3(x^2+10x+\boxed{?}^2)+72[/tex]
so hmm we're missing the guy on the right there... who may that be?
well, we know the middle term is 10x, wait a minute, 10x is just 2 * 5 * x
so, if the guy on the left is "x", the other guy must be "5", 2*5*x = 10x
now, what we do is, we add 5²
however, bear in mind that, all we're doing is, borrowing from our very good friend Mr Zero, 0
so, if we add 5², we also have to subtract 5², so +5² - 5²
let's do so
[tex]\bf g(x)=3(x^2+10x)+72\implies g(x)=3(x^2+10x\boxed{+5^2-5^2})+72 \\\\\\ \textit{let's take out the negative from the group} \\\\\\ g(x)=3(x^2+10x+5^2)+\boxed{3(-5^2)}+72 \\\\\\ g(x)=3(x^2+10x+5^2)-75+72\implies g(x)=3(x+5)^2-3 \\\\\\ g(x)=3[x-(-5)]^2-3[/tex]
[tex]\bf \qquad \textit{parabola vertex form}\\\\ \begin{array}{llll} y=a(x-{{ h}})^2+{{ k}} \end{array} \qquad\qquad vertex\ ({{ h}},{{ k}})\\\\ -------------------------------\\\\ \begin{array}{lcclll} g(x)=3[x-&(-5)]^2&-3\\ &\uparrow &\uparrow \\ &h&k \end{array}[/tex]
is a perfect square trinomial
now, let's take a closer look at the middle guy
is just 2 * guy on the left * guy on the right
so the middle term is just the product of the two terms of the binomial, without the exponent, or square rooted, and 2
alrite... that said.... now let's do some grouping
[tex]\bf g(x)=3x^2+30x+72\implies g(x)=(3x^2+30x)+72 \\\\\\ g(x)=3(x^2+10x)+72\implies g(x)=3(x^2+10x+\boxed{?}^2)+72[/tex]
so hmm we're missing the guy on the right there... who may that be?
well, we know the middle term is 10x, wait a minute, 10x is just 2 * 5 * x
so, if the guy on the left is "x", the other guy must be "5", 2*5*x = 10x
now, what we do is, we add 5²
however, bear in mind that, all we're doing is, borrowing from our very good friend Mr Zero, 0
so, if we add 5², we also have to subtract 5², so +5² - 5²
let's do so
[tex]\bf g(x)=3(x^2+10x)+72\implies g(x)=3(x^2+10x\boxed{+5^2-5^2})+72 \\\\\\ \textit{let's take out the negative from the group} \\\\\\ g(x)=3(x^2+10x+5^2)+\boxed{3(-5^2)}+72 \\\\\\ g(x)=3(x^2+10x+5^2)-75+72\implies g(x)=3(x+5)^2-3 \\\\\\ g(x)=3[x-(-5)]^2-3[/tex]
[tex]\bf \qquad \textit{parabola vertex form}\\\\ \begin{array}{llll} y=a(x-{{ h}})^2+{{ k}} \end{array} \qquad\qquad vertex\ ({{ h}},{{ k}})\\\\ -------------------------------\\\\ \begin{array}{lcclll} g(x)=3[x-&(-5)]^2&-3\\ &\uparrow &\uparrow \\ &h&k \end{array}[/tex]